Molecular analysis of peripheral lung adenocarcinoma in brush cytology obtained by EBUS plus fluoroscopy‐guided bronchoscopy. Issue 10 (6th October 2018) - Sánchez‐Font, Albert; Chalela, Roberto; Martín‐Ontiyuelo, Clara; Albero‐González, Raquel; Dalmases, Alba; Longarón, Raquel; Alonso‐Espinaco, Virginia; Curull, Víctor; Bellosillo, Beatriz; Pijuan, Lara
Abstract : BACKGROUND: More than 60% of patients with lung cancer are diagnosed at advanced stages. The introduction of targeted therapies requires molecular diagnosis to guide treatment. The aim of this study was to evaluate the feasibility of performing mutational analysis with brushing specimens obtained by radial‐miniprobe endobronchial ultrasound (R‐EBUS) plus fluoroscopy‐guided bronchoscopy in patients with peripheral pulmonary adenocarcinoma. METHODS: Brushing specimens were deposited on cytological slides and were conserved in Roswell Park Memorial Institute (RPMI) culture medium. DNA was isolated to perform a mutational analysis with real‐time quantitative polymerase chain reaction and Sanger sequencing for epidermal growth factor receptor ( EGFR ) and Kirsten rat sarcoma viral oncogene homolog ( KRAS ). RESULTS: Thirty patients with adenocarcinoma were prospectively included. In 100% of the patients, the molecular study was viable with brushing specimens. In 16 (53.3%), KRAS or EGFR mutations were detected: 10 KRAS mutations (33.3%) and 6 EGFR mutations (20%). In a comparison with histological samples, a correlation of 86.6% was detected, and only 2 patients with wild‐type results from brushing specimens presented with an EGFR mutation in histological samples. CONCLUSIONS: Brushing specimens conserved in RPMI medium and obtained by R‐EBUS plus fluoroscopy‐guided bronchoscopy are valid for molecular studies. They allow the detection of EGFR / KRAS mutations in patients with peripheral adenocarcinoma. In addition, invasive techniques are avoided, the risk of complications is reduced, and the obtained samples are optimized.